The Securitization of the Kurdish Minority in Turkey: Ontological Insecurity and Elite's Power Struggle as Reasons of the Recent Re‐Securitization. (8th November 2016) - Geri, Maurizio
Abstract: This article analyzes the treatment of the Kurdish minority by the government of Turkey. The uninterrupted power of the AKP (Justice and Development Party/ Adalet ve Kalkınma Partisi ) that since 2002 has created a de facto dominant party democracy (today going toward totalitarianism) and is implementing a strategy of securitization (Buzan, Waever, & de Wilde, 1998) of the issue of the Kurdish minority since the interruption of the ceasefire with the PKK (Kurdistan Workers' Party) in July 2015. The article argues that this strategy has been implemented for three main reasons: the reduced ontological security (Giddens, 1991) of Turkey because of the recent violent conflicts in Syria and Iraq, the risk of loss of power of the ruling party and the elites (Snyder, 2000) because of the recent entrance in the Parliament by the HDP (People's Democratic Party, a pro‐Kurdish party), and the ideological threat posed by HDP to the AKP regime (a left‐wing progressive ideology opposed to the moderate Islamist ideology of AKP). The purpose of this study is to fill a research gap in the area of why the post‐July 2015 era constitutes a new context shaping the AKP's perception and management of the Kurdish issue. The methodology followed in this research is a qualitative case study analysis based on process tracing of the recent Turkish treatment of the Kurdish minority and, in particular, the recent events of the second part of 2015 and the beginning of 2016. The article starts with a brief historical overview of Turkish democracy and a theoretical overview on the securitization theory. Then, it analyzes the past and current securitization of the Kurdish issue, arguing that the causes of the recent intensification of this securitization since the summer of 2015 have to be found in these three factors: the low level of ontological security of the state; the fear of losing the power by the AKP ruling elite; and the threat to the political ideology of the AKP posed by the HDP.